Reaction Products of β-Aminopropioamidoximes Nitrobenzenesulfochlorination: Linear and Rearranged to Spiropyrazolinium Salts with Antidiabetic Activity - Lyudmila Kayukova; Anna Vologzhanina; Pavel Dorovatovskii; Gulnur Baitursynova; Elmira Yergaliyeva; Ayazhan Kurmangaliyeva; Zarina Shulgau; Sergazy Adekenov; Zhanar Shaimerdenova; Kydymolla Akatan (Molecules, 2022)
Nitrobenzenesulfochlorination of β-aminopropioamidoximes leads to a set of products depending on the structure of the initial interacting substances and reaction conditions. Amidoximes, functionalized at the terminal C atom with six-membered N-heterocycles (piperidine, morpholine, thiomorpholine and phenylpiperazine), as a result of the spontaneous intramolecular heterocyclization of the intermediate reaction product of an SN2 substitution of a hydrogen atom in the oxime group of the amidoxime fragment by a nitrobenzenesulfonyl group, produce spiropyrazolinium ortho- or para-nitrobenzenesulfonates. An exception is ortho-nitrobenzenesulfochlorination of β-(thiomorpholin-1-yl)propioamidoxime, which is regioselective at room temperature, producing two spiropyrazolinium salts (ortho-nitrobezenesulfonate and chloride), and regiospecific at the boiling point of the solvent, when only chloride is formed. The para-Nitrobezenesulfochlorination of β-(benzimidazol-1-yl)propioamidoxime, due to the reduced nucleophilicity of the aromatic β-amine nitrogen atom, is regiospecific at both temperatures, and produces the O-para-nitrobenzenesulfochlorination product. The antidiabetic screening of the new nitrobezenesulfochlorination amidoximes found promising samples with in vitro α-glucosidase activity higher than the reference drug acarbose. 1H-NMR spectroscopy and X-ray analysis revealed the slow inversion of six-membered heterocycles, and experimentally confirmed the presence of an unfavorable stereoisomer with an axial N–N bond in the pyrazolinium heterocycle.